2002
DOI: 10.1108/13612020210429458
|View full text |Cite
|
Sign up to set email alerts
|

Body scanning

Abstract: Describes research designed to examine the effects of subject positioning on the accuracy of body scan data. A body measurement system developed by the Textile Clothing Technology Corporation was used to acquire two scans from each of 72 subjects. The subjects were instructed to continue to breathe normally and stand with their feet shoulder‐width apart. The two scans were compared and statistical analysis was performed to determine the precision of the results and whether this lack of standardization affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 10 publications
1
7
0
4
Order By: Relevance
“…ISO 20685 stipulates that "for all postures, quiet respiration (normal breathing) should be adopted". This is in line with the findings of the study conducted by Mckinnon and Istook (Mckinnon and Istook, 2002), who scanned subjects holding their breath at different inhalation levels and when breathing normally. They found that humans are unable to reliably replicate a certain respiration level and that continuing breathing normally during the scanning process compromises the data integrity least.…”
Section: Factors Influencing Precision Of Data Captured With 3d Body supporting
confidence: 91%
See 3 more Smart Citations
“…ISO 20685 stipulates that "for all postures, quiet respiration (normal breathing) should be adopted". This is in line with the findings of the study conducted by Mckinnon and Istook (Mckinnon and Istook, 2002), who scanned subjects holding their breath at different inhalation levels and when breathing normally. They found that humans are unable to reliably replicate a certain respiration level and that continuing breathing normally during the scanning process compromises the data integrity least.…”
Section: Factors Influencing Precision Of Data Captured With 3d Body supporting
confidence: 91%
“…Accuracy and precision of the data ascertained with 3D body scanners are influenced by the factors listed in Figure 1 and are broadly split into two main categories: Technical Variability and Human Variability Mochimaru, 2011, 2008;Mckinnon and Istook, 2002): Previous studies have shown that body dimensions extracted from 3D body scans regularly fail to satisfy the accuracy requirements laid down in ISO 20685 for the use in anthropometric databases (Han et al, 2010;Mckinnon and Istook, 2002). Thus, those of the aforementioned factors need to be identified, which potentially inhibit achieving the desired level of accuracy and precision.…”
Section: Factors Influencing Precision Of Data Captured With 3d Body mentioning
confidence: 99%
See 2 more Smart Citations
“…When measured manually, the physical contact and proximity to the measurer might influence body posture and contraction of the trunk area of the probands resulting in smaller values (Jaeschke, Steinbrecher & Pischon, 2015). In the case of hip circumference, the standard scanning posture with legs hip-width apart might enlarge the resulting measurements (McKinnon & Istook, 2002). In general, the hand-held tape measurements have a tendency to compress the circumference caused by too much tension and thus reduce the values (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%